Islamic Education Management Patterns In Mandailing Natal: Case Studi In Pesantren Musthofawiyah Purbabaru - Agusnan Agusnan; Solihah Titin Sumanti; Yusnaili Budianti (Institut Agama Islam An-Nawawi Purworejo, 2023)
This research examines the pattern of Islamic Education Management in Mandailing Natal; this research was carried out at the Musthofawiyah Islamic Boarding School in Purbabaru. The approach used in this study is qualitative with a descriptive system. A descriptive approach is a method that describes or provides an overview of the object under study through data or samples. Data sources used are primary and secondary data; data collection techniques include interviews, documentation, and observation. As for the research results, The curriculum pattern at the Musthofawiyah Purbabbaru Islamic boarding school is very thick with maintaining the educational design; Syekh Musthofa Husen Nasution formed the initial tradition because starting from the change of the pesantren leadership until now, the curriculum has been held the same as the initial establishment of the Musthofawiyah Islamic Boarding School Purbabaru, the teaching pattern of the Musthofawiyah Islamic Boarding School Purbabbaru using four teaching patterns, especially Islamic religious studies, namely in the form of speaking methods, question and answer, dictation (Imla') and discussion, the facilities and infrastructure of the Mustofawiyah Islamic Boarding School experienced many changes in leadership from time to time both physically and non-physically, only a few secondary needs alone are still not enough.